Clover Mite Bryobia praetiosa Koch - Celina Gomez; Russell F. Mizell, III (EDIS)
EENY-437, a 4-page illustrated fact sheet by Celina Gomez and Russell F. Mizell III, is part of the Featured Creatures collection. It describes this plant-feeding mite found in landscapes that can invade homes in large numbers after heavy rains, excessive heat, or changes in the season. Includes references. Published by the UF Department of Entomology and Nematology, September 2008.